Poems from Iqbal : Renderings in English Verse with Comparative Urdu Text - Iqbal, Muhammad, Sir; Translated by Kiernan, V. G. (Karachi Oxford University Press, 2015)
Allama Muhammad Iqbal was acknowledged during his lifetime as the most important poet of Muslim India in the twentieth century, both for the quality of his verse and for the influence exercised by his ideas. This volume contains a rendering in English of over a hundred poems chosen from the four collections of Iqbal's poetry written in Urdu, which include religious, lyrical, satirical and other themes. The English versions are accompanied by the original text.
Include Notes.
Renderings in English Verse with Comparative Urdu Text.
Keywords: Urdu poetry -- Iqbal, Muhammad, Sir, 1877-1938 -- Urdu poetry - in English